2017
DOI: 10.1038/s41531-017-0013-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the safety and immunomodulatory effects of sargramostim in a randomized, double-blind phase 1 clinical Parkinson’s disease trial

Abstract: A potential therapeutic role for immune transformation in Parkinson’s disease evolves from more than a decade of animal investigations demonstrating regulatory T cell (Treg) nigrostriatal neuroprotection. To bridge these results to human disease, we conducted a randomized, placebo-controlled double-blind phase 1 trial with a well-studied immune modulator, sargramostim (granulocyte-macrophage colony-stimulating factor). We enrolled 17 age-matched non-Parkinsonian subjects as non-treated controls and 20 Parkinso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 109 publications
(128 citation statements)
references
References 52 publications
7
118
2
Order By: Relevance
“…These results provide support for the proposed mechanism of action of AZD3241 on microglia and encourage further studies evaluating its potential to modify the disease course of PD as well as other neurodegenerative disorders. A small double‐blind trial of sargramostim, a recombinant granulocyte macrophage colony stimulating factor, demonstrated modest improvements in clinical, magnetoencephalography (MEG)‐recorded cortical activities and regulatory T cell number and function compared to placebo or pretreatment states . A review of http://clinicaltrials.gov shows a number of other terminated or completed but unreported studies of treatments directed at neuroinflammation.…”
Section: Targets For Disease Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…These results provide support for the proposed mechanism of action of AZD3241 on microglia and encourage further studies evaluating its potential to modify the disease course of PD as well as other neurodegenerative disorders. A small double‐blind trial of sargramostim, a recombinant granulocyte macrophage colony stimulating factor, demonstrated modest improvements in clinical, magnetoencephalography (MEG)‐recorded cortical activities and regulatory T cell number and function compared to placebo or pretreatment states . A review of http://clinicaltrials.gov shows a number of other terminated or completed but unreported studies of treatments directed at neuroinflammation.…”
Section: Targets For Disease Modificationmentioning
confidence: 99%
“…A small double-blind trial of sargramostim, a recombinant granulocyte macrophage colony stimulating factor, demonstrated modest improvements in clinical, magnetoencephalography (MEG)-recorded cortical activities and regulatory T cell number and function compared to placebo or pretreatment states. 67 A review of clinicaltrials.gov shows a number of other terminated or completed but unreported studies of treatments directed at neuroinflammation. ViNeuro, a compound said to have a variety of immunomodulating functions (increases the activities of T cells, B cells, and natural killer (NK) cells and enhances mitochondrial antioxidant status) in various tissues including brain, was studied in a triple-blind randomized controlled clinical trial for safety and efficacy (NCT00517842, completed in September 2008).…”
Section: Other Treatment Categoriesmentioning
confidence: 99%
“…It improves the function of neuroprotective, regulatory T cells. In two placebo‐controlled double‐blind phase I trials, granulocyte‐macrophage colony‐stimulating factors served as a neuroprotective agent in PD by increasing the numbers and improving the function of regulatory T cells …”
Section: Current Developments: Neuroprotection and Neurorestorationsmentioning
confidence: 99%
“…In two placebo-controlled doubleblind phase I trials, granulocyte-macrophage colony-stimulating factors served as a neuroprotective agent in PD by increasing the numbers and improving the function of regulatory T cells. 71,72 Epidemiological evidence suggests a slightly protective effect of the ß2-agonist salbutamol on the risk to develop PD 73 especially for long-acting formulations, although this is not without controversy. The ß2-agonists may exert an inhibitory effect on inflammatory processes and may, thus, be capable of modulating inflammatory conditions.…”
Section: Current Developments: Neuroprotection and Neurorestorationsmentioning
confidence: 99%
“…The XCMS systems biology results implicated tumor progression with biofilm development via polyamine biosynthesis 9 . This platform has also been used on a phase I clinical trial drug for a Parkinson’s disease immunotherapy that was found to target the tryptophan pathway and later validated with targeted metabolomics 20 . More recently, cellular responses to chemical exposure of a xenoestrogen on breast cancer cells have been studied and found to alter tRNA charging and ribonucleoside salvage pathways 21 .…”
Section: Introductionmentioning
confidence: 99%